2014
DOI: 10.1063/1.4896318
|View full text |Cite
|
Sign up to set email alerts
|

Design of time-delayed connection parameters for inducing amplitude death in high-dimensional oscillator networks

Abstract: The present paper studies time-delayed-connection induced amplitude death in high-dimensional oscillator networks. We provide two procedures for design of a coupling strength and a transmission delay: these procedures do not depend on the topology of oscillator networks (i.e., network structure and number of oscillators). A graphical procedure based on the Nyquist criterion is proposed and then is numerically confirmed for the case of five-dimensional oscillators, called generalized Rössler oscillators, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…Huddy and Skufca reported that delay connections can induce the stabilization of an operating point in coupled dc bus systems [22], This stabilization is referred to as time-delay-induced amplitude death, which is a well-known phenomenon in the field of nonlinear science [31][32][33][34]. The stability of amplitude death is closely related to that of our decentralized delayed-feedback controller (14).…”
Section: Discussionmentioning
confidence: 93%
“…Huddy and Skufca reported that delay connections can induce the stabilization of an operating point in coupled dc bus systems [22], This stabilization is referred to as time-delay-induced amplitude death, which is a well-known phenomenon in the field of nonlinear science [31][32][33][34]. The stability of amplitude death is closely related to that of our decentralized delayed-feedback controller (14).…”
Section: Discussionmentioning
confidence: 93%
“…with a diagonal transformation matrix T [22,23,28,29]. The transformation δx(n) = T ξ(n) allows us to obtain…”
Section: Stability Analysismentioning
confidence: 99%
“…. , N) of asymmetric matrix M := I N − C are always within the range ρ q ∈ [0, 2] [22,23,28,29], i.e.,…”
Section: Delay-coupled Bernoulli Map Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyragas (Pyragas, 1992) (Nakajima, 1997) (amplitude death) (Konishi, 2005) A (Sugitani et al, 2014) (2) τ(t) …”
Section: N   ẋ I (T) = Ax I (T) + F (X I (T)) + G(x I (T))u I (T)mentioning
confidence: 99%